Analytical performance of automated platelet counts and impact on platelet transfusion guidance in patients with acute leukemia - Chaicharoen Tantanate (2020)
© 2019, © 2019 Medisinsk Fysiologisk Forenings Forlag (MFFF). The aim of this study was to evaluate the performance of automated impedance platelet counts by Beckman Coulter LH780 (PLT-LH), Sysmex XN-3000 (PLT-XNi) and fluorescence method by Sysmex XN-3000 (PLT-F) in patients with acute leukemia. Blood specimens were subjected to platelet measurements by evaluated methods and then compared against the international reference method (IRM). Eighty-two blood specimens were included. Bland–Altman plots of the differences between the evaluated methods and IRM demonstrated mean biases of PLT-LH, PLT-XNi and PLT-F of 9 × 10 9 /L, 11 × 10 9 /L and 2 × 10 9 /L, respectively. For platelet transfusion guidance, all evaluated methods had acceptable accuracy. For platelet transfusion guidance, the sensitivities of PLT-LH, PLT-XNi and PLT-F were 33.3, 25.0 and 83.3%, respectively, at a transfusion threshold of 10 × 10 9 /L, and 73.1, 61.5 and 84.6%, respectively, at transfusion threshold of 20 × 10 9 /L. High blast count was associated with inaccurate PLT-LH and PLT-XNi. In conclusion, the PLT-F demonstrated excellent performance for diagnosis of thrombocytopenia and for platelet transfusion guidance in the evaluated specimens from acute leukemia patients. With respect to clinical relevance, careful blood smear review is necessary in case of high blast counts.